Rancang Bangun Tracker Surya Sumbu Ganda Berbasis Raspberry Pi - M Permadi Yosa Nugraha; Abdul Rakhman; Irma Salamah (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
Solar energy is now a very important means of renewable energy resources. With sun tracking, it is more effective to produce more energy because solar panels can maintain a profile perpendicular to sunlight. Although the initial cost of setting up a tracking system is quite high, there are cheaper options that have been proposed from time to time. Light Dependent Resistors (LDRs) are used to detect sunlight. The solar panel is positioned where it can receive maximum light. Compared to other motors, servo motors are able to maintain torque at high speed. The tracker is in the form of a double or single axis. Dual trackers are more efficient because they track sunlight from both axes. This project is designed for low power and portable applications. Therefore, it is suitable for use in rural areas. In addition, the effectiveness of the output power collected by sunlight increases.